Durability performance of pervious concrete containing rice husk ash and calcium carbide: A response surface methodology approach. (June 2021) - Adamu, Musa; Ayeni, Kingsley Oyime; Haruna, Sadi Ibarahim; Ibrahim Mansour, Yasser El-Husseini; Haruna, Sani
Abstract: Pervious concrete is a special type of concrete used for stormwater management due to its high porosity and permeability. However, the large pores in pervious concrete resulted to its low mechanical strength. Moreover, the emissions of greenhouse gases from Portland cement (PC) production are high and contribute to climate changes leading to climate change. Calcium carbide waste (CCW) and rice husk ash (RHA) were used as supplementary cementitious material to partially replace Portland cement by 5%, 10 %, 15 %, and 20 %. Response Surface Methodology was used to design the experiments and develop models for predicting the water absorption and permeability of PC. The properties of the developed pervious concrete like water permeability and water absorption were investigated. The most vital property of the pervious concrete is water-permeability. The result findings showed that both RHA and CCW have negative effect on the durability of PC, with RHA having the worst effect. The RSM models developed showed a high degree of correlation between the variables and the responses. The optimized variables which give the best durability performance was a combination of 0% RHA and 5% CCW having the following properties, water permeability between 0.96 cm/s and water absorption of 4.338 %. The developed models can be used for predicting the permeability and water absorption capacity of pervious concrete.